Direct teaching of vocabulary after listening: is it worth the effort and what method is best?. Issue 3 (3rd July 2017) - Hennebry, Mairin; Rogers, Vivienne; Macaro, Ernesto; Murphy, Victoria
Abstract : This paper reports a study comparing the effects of vocabulary instruction on recognition and recall through provision of either an L1 equivalent or an L2 (French) definition. Instruction was in the context of a focus-on-meaning listening activity. The study employed a quasi-experimental design, involving 262 Year 9 learners of French in seven intact classes. Results indicate that brief vocabulary instruction after the listening activity led to more effective recall than a listening-only condition. Gains were found in favour of the L1 equivalent condition over the L2 definition condition for higher and lower proficiency students. Pedagogical implications for this type of lexical focus in the context of a meaning-focused activity are discussed.